The development of pevonedistat in myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML): hope or hype?. (July 2022) - Snow, Anson; Zeidner, Joshua F.
Myelodysplastic syndrome (MDS) is a clonal hematopoietic stem cell disorder clinically defined by cytopenias, bone marrow failure, and an increased risk of progressing to acute myeloid leukemia (AML). Traditionally, first-line treatment for patients with higher-risk MDS has been hypomethylating agents (HMAs). However, these agents have modest clinical activity as single agents. A one-size-fits-all treatment paradigm is insufficient for such a heterogeneous disease in the modern era of precision medicine. Several new agents have been developed for MDS with the hopes of improving clinical outcomes and survival. Pevonedistat is a first-in-class, novel inhibitor of neuronal precursor cell-expressed developmentally down-regulated protein-8 (NEDD8) activating enzyme (NAE) blocking the neddylation pathway leading to downstream effects on the ubiquitin–proteosome pathway. Pevonedistat ultimately leads to apoptosis and inhibition of the cell cycle in cancer cells. Studies have demonstrated the safety profile of pevonedistat, leading to the development of multiple trials investigating combination strategies with pevonedistat in MDS and AML. In this review, we summarize the preclinical and clinical rationale for pevonedistat in MDS and AML, review the clinical data of this agent alone and in combination with HMAs to date, and highlight potential future directions for this agent in myeloid malignancies.